Evaluation of antibacterial textile covered by layer-by-layer coating and loaded with chlorhexidine for wound dressing application - Aubert-Viard F. (2019)
This research was funded by FONDECYT-CONCYTEC (grant contract number 238-2015-FONDECYT).